Examining the effectiveness of cognitive therapies for children with ADHD - Chew, Chelsea Liang Ru. (2012)
The purpose of this exploratory study was to use Electroencephalogram (EEG) recordings to examine the relationships between the maintenance of sustained attention a cross various academic tasks and the presentation of different background music amongst individuals diagnosed with Attention Deficit (Hyperactivity) Disorder(ADHD). Specifically, the present researchs ought to explore the differences in sustained attention and ease of paying attention and enjoyability across Reading, Reading Comprehension, Reading Comprehension with recall (with working memory load), Numerical Operations, and the presentation of silence, classical music, pop music, and sounds from television programs. Differences in sustained attention were measured using EEG recordings while the participants rated the ease of paying attention and enjoyability across the different sound conditions on the different tasks. Twelve individuals with ADHD participated in this study. Individuals with ADHD were found to be better able to sustain attention with pop music in the background in a task that did not have a working memory load, reading.